Contribution of the murine and primate models to the study of arenaviral diseases and hemorrhagic fevers - Rodas G., Juan David; Hewson, Roger; Salvato, María S. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary This manuscript is an inedited part of my PhD dissertation, based on historical and recent findings on animal models, that was presented as part of the requirements to fulfill the conditions to become a philosophical doctor on Veterinary Sciences at the University of Wisconsin on October of 2003.The current mini-review written on a free-version style, underlines some of the cornerstones of immunology as a science, understood thanks to the use of the Lymphocytic Choriomeningitis virus (LCMV) experimentally and naturally infected mouse model. It should suffice to say that there have been two Nobel prices of Medicine for discoveries made through the employment of this animal model, in order to recognize the right importance to it. In addition, several laboratories, Dr. Salvato´s among them, have also employed the LCMV-infected Rhesus monkey model as a tool to unravel the mysteries of arenaviral hemorrhagic fever, and particularly the physiopathology of Lassa disease in humans. Here I show some of the knowledge generated through the study of both animal infections.